2013
DOI: 10.3109/10717544.2012.742938
|View full text |Cite
|
Sign up to set email alerts
|

Development of a reservoir-type transdermal delivery system containing eucalyptus oil for tetramethylpyrazine

Abstract: The purpose of this study was to formulate a reservoir-type transdermal delivery system (TDS) for 2,3,5,6-tetramethylpyrazine (TMP) to enable the delivery of a sufficient dose through human skin to achieve an effective therapeutic plasma concentration. To improve the penetration of TMP in the reservoir-type TDS, several chemical penetration enhancers were investigated using in vitro rat dorsal skin permeation studies. Eucalyptus oil was found to enhance the permeation of TMP to the greatest extent, with the op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Moreover, essential oils (EOs) and their volatile constituents have also been identified as one promising group of candidates to be employed as clinically acceptable PEs. Until now, EOs have been shown to be successful in delivering a range of different drugs across the skin, including vitamins (Valgimigli et al 2012), estradiol (Monti et al 2002), labetolol hydrochloride (Jain et al 2008), trazodone hydrochloride (Das et al 2006), tetramethylpyrazine (Shen et al 2013), carvedilol (Amin et al 2008), 5-fluorouracil (5-FU) (Lan et al 2014a), flurbiprofen (Zhang et al 2006;Charoo et al 2008), diclofenac sodium (Akbari et al 2015), indomethacin (Lan et al 2014a) and ibuprofen (Luo et al 2007;Shen et al 2007;Khan et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, essential oils (EOs) and their volatile constituents have also been identified as one promising group of candidates to be employed as clinically acceptable PEs. Until now, EOs have been shown to be successful in delivering a range of different drugs across the skin, including vitamins (Valgimigli et al 2012), estradiol (Monti et al 2002), labetolol hydrochloride (Jain et al 2008), trazodone hydrochloride (Das et al 2006), tetramethylpyrazine (Shen et al 2013), carvedilol (Amin et al 2008), 5-fluorouracil (5-FU) (Lan et al 2014a), flurbiprofen (Zhang et al 2006;Charoo et al 2008), diclofenac sodium (Akbari et al 2015), indomethacin (Lan et al 2014a) and ibuprofen (Luo et al 2007;Shen et al 2007;Khan et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the effect of the type of polymer used [51], the amount of the polymer used [52], and the type and concentration of plasticizer used [2] can all impact its activity, and there are some contradictory reports regarding its efficacy. Although Yaqoob et al [51], Akram et al [50], and Zeng et al [52] found the penetration enhancement effect of eucalyptus oil to be less than isopropyl myristate [IPM] and Azone from matrix patches of metoprolol, glimepride, and elemene, respectively, El-Nabarawi et al [2], Shen et al [53], and Sharma and Mehra [13] reported the opposite. They found that eucalyptus oil exerted the highest penetration enhancement effect compared with other penetration enhancers from transdermal patches of sumatriptan, tetramethylpyrazine, and celecoxib.…”
Section: Eucalyptus Oilmentioning
confidence: 99%
“…The transdermal flux rate from the patch increased steadily, reaching a maximum value of 459 µg/cm 2 /h at 3 to 5 h, and decreased slowly to a rate of about 283 µg/cm 2 /h from 12 to 24 h. This phenomenon has also been observed in an estradiol transdermal reservoir membrane system, which showed that the patients' C max of estradiol at 30 h corresponded with the maximum Estradiol flux through human skin at 20 to 30 h. 25) In our previous formulation studies on TMP transdermal patch, eucalyptus oil was selected as the penetration enhancer because of superior efficacy when compared to azone and menthol. 26) eucalyptus oil contains more than 80% cineole, a well-known skin penetration enhancer. Cineole enhances skin permeation by disrupting the inter-lamellar hydrogen-bonding network of the polar head group region in the stratum corneum bilayer, which facilitates the partition and permeation of small polar molecules through the skin.…”
Section: Discussionmentioning
confidence: 99%